2014
DOI: 10.1177/0194599813520290
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Endonasal Transpterygoid Transmaxillary Approach to the Infratemporal and Upper Parapharyngeal Tumors

Abstract: The purely endoscopic endonasal technique may provide a minimally invasive and safe approach to radically resect selected tumors involving the ITF and UPS. Larger case series and longer follow-up are needed to validate the reproducibility and efficacy of this technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
110
2
7

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 106 publications
(120 citation statements)
references
References 35 publications
1
110
2
7
Order By: Relevance
“…16 Battaglia et al reported 1 case of gross-total resection of a sinonasal chondrosarcoma through a transpterygoid transmaxillary approach, without complications. 2 We strongly believe that chondrosarcomas involving the posterior fossa and CPA are amenable to treatment with an EEA approach, with excellent results in terms of resection, while minimizing surgical morbidity, as evidenced by the current series. The main characteristic of the endonasal approach is its ability to reach the petroclival synchondrosis with little to no morbidity for the patient.…”
Section: 4mentioning
confidence: 57%
“…16 Battaglia et al reported 1 case of gross-total resection of a sinonasal chondrosarcoma through a transpterygoid transmaxillary approach, without complications. 2 We strongly believe that chondrosarcomas involving the posterior fossa and CPA are amenable to treatment with an EEA approach, with excellent results in terms of resection, while minimizing surgical morbidity, as evidenced by the current series. The main characteristic of the endonasal approach is its ability to reach the petroclival synchondrosis with little to no morbidity for the patient.…”
Section: 4mentioning
confidence: 57%
“…A criticism of this approach pertains to its relevance in the setting of expanded endoscopic approaches (including transpterygoid, trans-fovea ethmoidalis [2831]). Certainly, access to the areas of the skull base afforded by expanded endonasal approaches and even supraorbital keyhole craniotomies can be obtained.…”
Section: Discussionmentioning
confidence: 99%
“…Endoscopic endonasal dissections of the sino-orbitocranial interface (11,12) and of the pterygopalatine and infratemporal fossa via a transpterygoid approach were performed as previously described (6). Extended exposure of the middle cranial fossa floor also was achieved through an endoscopic transnasal route, reaching the same areas previously exposed through the transorbital approach.…”
Section: Preclinical Studymentioning
confidence: 99%